Ceramic Matrix-Stamps of the Medieval Period from the Collection of the State Museum of the History of Uzbekistan - Tokhir Norkobilov (International Journal on Integrated Education, 2022)
This article is devoted to the study of matrices used for the manufacture of stamped ceramics, which is stored in the archaeological fund of the State Museum of the History of Uzbekistan. These studies show the high level of skill of medieval ceramists of Central Asia.